The Interactions of Small Proline-Rich Proteins with Late Cornified Envelope Proteins are Involved in the Pathogenesis of Psoriasis - Tian S; Chen S; Feng Y; Li Y (Dove Medical Press, 2021)
Siyu Tian, Shuming Chen, Yongyi Feng, Yong Li School of Life Sciences, Xiamen University, Xiamen, People's Republic of ChinaCorrespondence: Yong LiSchool of Life Sciences, Xiamen University, Xiamen, Fujian, 361005, People's Republic of ChinaTel +86-592-2182510Fax +86-592-2182560Email yongli@xmu.edu.cnPurpose: Psoriasis is a common cutaneous disease with multiple characteristics including inflammation and aberrant keratinocyte proliferation. However, the pathogenesis of psoriasis is not completely clear yet. The objective of this study is to perform an in-depth analysis of the association between SPRR and LCE in the pathogenesis of psoriasis.Methods: In this study, we explore the differentially expressed genes (DEGs) in psoriasis by analyzing different gene expression profiles obtained from the Gene Expression Omnibus (GEO) database. The DEGs were examined using gene ontology (GO) functional enrichment analysis and protein-protein interactions (PPI) network. Correlation analysis in R studio software was used to analyze the association between SPRR and LCE genes. Further, potential direct protein-protein interactions between SPRR proteins and LCE3D were verified by co-localization observations and co-immunoprecipitation (CO-IP) assays in 293T cells. Also, the expression levels of SPRR and LCE genes were detected in lesional skin of the IMQ-induced psoriasiform dermatitis mice using RT-PCR.Results: Interestingly, the small proline-rich (SPRR) and late cornified envelope (LCE) genes were identified as a module in the constructed PPI network. And the analysis of the gene expression profile GSE63684 showed that both SPRR family and LCE family genes were significantly upregulated in imiquimod (IMQ) induced psoriasiform dermatitis mice. Also, the correlation analysis in R studio software recognized the association of SPRR and LCE genes, which were further verified by co-localization and co-immunoprecipitation (CO-IP) assays in 293T cells, and the results show that the direct interactions between SPRR2 and LCE3D. Notably, we also found that the expression levels of SPRR and LCE genes were significantly increased in the IMQ-induced psoriasiform dermatitis mice, while specifically decreased under the tazarotene cream treatment, indicating that the SPRR and LCEs were regulated simultaneously in psoriasis.Conclusion: In summary, our study found that interactions between SPRR proteins and LCE proteins may provide new insights into the pathogenesis of psoriasis.Keywords: psoriasis, bioinformatics analysis, interaction, SPRR, LCE